2011
DOI: 10.1007/s11605-011-1504-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Insulin-Like Growth Factor 1 Receptor is Implicated in Resistance to the Cytostatic Effect of Gefitinib in Colorectal Cancer Cells

Abstract: We investigated the potential mechanisms of the uncoupling of EGFR from its downstream signals in colorectal cancer (CRC) cells. Alternative growth factor receptors and regulation of downstream pathways in different gefitinib-responsive cell lines were determined. Basal insulin-like growth factor receptor-1β (IGFR-1β) phosphorylation was undetectable or present at very low levels in highly gefitinib-responsive cell lines and was present at strikingly high levels in less responsive cell lines. Further analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…Indeed, preclinical evidence suggests that gefitinib can induce downstream activation of the Akt and MAPK pathways in colorectal cancer cell lines by triggering phosphorylation of IGF-1R or heterodimerization of EGFR and IGF-1R (15). In a separate study, combined downregulation of both EGFR and IGF-1R in colorectal cancer cell lines was shown to decrease cell proliferation and induce apoptosis more effectively than downregulation of either receptor alone (16).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, preclinical evidence suggests that gefitinib can induce downstream activation of the Akt and MAPK pathways in colorectal cancer cell lines by triggering phosphorylation of IGF-1R or heterodimerization of EGFR and IGF-1R (15). In a separate study, combined downregulation of both EGFR and IGF-1R in colorectal cancer cell lines was shown to decrease cell proliferation and induce apoptosis more effectively than downregulation of either receptor alone (16).…”
Section: Introductionmentioning
confidence: 97%
“…IGF-1R has also been implicated in the development of colorectal cancer (13,14), and it has been suggested that cross-talk between the EGFR and IGF-1R signaling pathways may be a mechanism by which colorectal cancer cells develop resistance to EGFR tyrosine kinase inhibitors (15). Indeed, preclinical evidence suggests that gefitinib can induce downstream activation of the Akt and MAPK pathways in colorectal cancer cell lines by triggering phosphorylation of IGF-1R or heterodimerization of EGFR and IGF-1R (15).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the induced activation of signaling pathway by targeted drug will drive resistance. In EGFR TKI erlotinib-resistant lung cancer cells and colon cancer cells, the induced insulin-like growth factor-I receptor activation is implicated in resistance to erlotinib [12,13]. However, whether the induced MET activation by EGFR inhibitors mediating resistance is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…HT29 cells express a 3-fold higher level of e-cadherin, a driver of contact inhibition of proliferation (36). HT29 cells have also been shown to be more resistant than HCT116 cells to strategies that use IGF-I receptor inhibition to control tumor cell growth (37). When grown as solid tumors, both cell types exhibited regions of chronic hypoxia in areas 100 to 150 mm from vessels, and both displayed a reduction in proliferation with distance from blood vessels.…”
Section: Discussionmentioning
confidence: 99%